The efficacy and safety of Sacubitril/Valsartan on pulmonary hypertension in hemodialysis patients - Zhao, Cong; Guo, Yanhong; Wang, Yulin; Wang, Liuwei; Yu, Lu; Liang, Yan; Zhai, Zihan; Tang, Lin (Frontiers in Medicine, 2022)
Background: Pulmonary hypertension (PH) is a common complication of end-stage renal disease which is associated with adverse outcomes including all-cause mortality and cardiovascular events. Recent studies have demonstrated that Sacubitril/Valsartan (Sac/Val) as an enkephalinase inhibitor and angiotensin II receptor blocker could reduce pulmonary artery systolic pressure (PASP) and improve the prognosis of patients with heart failure. However, whether Sac/Val is effective in hemodialysis (HD) patients with PH is essentially unknown. In this retrospective study, we aimed to evaluate the efficacy and safety of Sac/Val in the treatment of PH in HD patients. Methods: A total of 122 HD patients with PH were divided into Sac/Val group (n=71) and ARBs group (n=51) based on the treatment regimen. The PASP, other cardiac parameters measured by echocardiography, and cardiac biomarkers including N-terminal fragment of BNP (NT-proBNP) and cardiac troponin I (cTnI) were observed at baseline and 3 months after treatment. Results: There were no significant differences in the baseline characteristics between the two groups. PASP decreased significantly from 45(38, 54) to 28(21, 40) mmHg in Sac/Val group (p<0.001). PASP reduced from 41(37, 51) to 34(27, 44) mmHg in ARBs group (p<0.001), and the decrease was more pronounced in the Sac/Val group (p<0.001). In addition, improvements in the right atrial diameter (RAD), left ventricular diameter (LVD), left ventricular posterior wall thickness (LVPWT), left atrial diameter (LAD), pulmonary artery diameter (PAD), left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), left ventricular ejection fraction (LVEF), and fractional shortening (FS) were found in Sac/Val group (ps<0.05). After 3 months, LVD, LAD, LVEDV, LVESV, LVEF, SV, and PASP were significantly improved in Sac/Val group compared with ARBs group (ps<0.05). Significant reduction in NT-proBNP [35000(15000, 70000) pg/ml vs 7042(3126, 29060) pg/ml, p<0.001] and cTnI [0.056(0.031, 0.085) ng/ml vs 0.036(0.012, 0.056) ng/ml, p<0.001) were observed in Sac/Val group. No significant differences were observed in adverse events between the two groups (ps>0.05). Conclusion: Sac/Val seems to be an efficacious regimen in PH with favorable safety and has huge prospects for treating PH in HD patients.